Graduating University as a Woman with Down Syndrome: Reflecting on My Education - Rachel High (MDPI AG, 2021)
This paper reflects on the experience of being a woman with Down Syndrome who completed an undergraduate degree at an Australian university. This autoethnography is based on a year-long research project completed as part of my studies. I did a literature review about the experiences of other students with an intellectual disability at university. Then, I wrote about my own university experience. I found that the parts of my own educational journey were linked to each other like stepping-stones. Four main things came from my research: the importance of the journey before going to university; the isolation experienced by students in this situation; how stereotypes might affect students; and teaching methods that can be used to support students during their time at university. This experience changed me as a person. I gained skills and confidence whilst being at university, as well as the ability to see where I am going in life. This experience made me feel more part of society. While there were many wonderful parts, it was not an easy journey. People with an intellectual disability have a right to have an education. What makes the biggest difference is the way we are treated by other people. It would be good for students with an intellectual disability to be accepted and treated with respect. People may have a different way of learning, and it would be good if this was recognised.